Pendampingan Masyarakat dalam Pemenuhan Standar Rumah Sehat dan Layak Huni Berdasarkan Keputusan Menteri Pemukiman dan Prasarana Wilayah - Arbaningrum, Rizka; Wulandari Subagyo, Galih; Fredy Jhon Philip Sitorus; Ghiffari Mahardiansyah; Esmeralda Marisa Osang; Muhammad Izza Luthfi (BADAN PENERBIT STIEPARI PRESS, 2026)
A healthy house is understood as a form of housing designed to support the improvement of its occupants’ health standards. Thus, it can be said that a healthy home is a building for shelter and rest. To realize a house that can function properly, a healthy, safe, harmonious, and well-organized housing environment is required. The purpose of this assistance is to increase insight, knowledge, and improve understanding, regarding healthy, habitable homes and legal awareness regarding home ownership, in order to realize healthy and decent housing governance. The Sawah Baru Village area located in Ciputat District, South Tangerang City is the location for implementing healthy and habitable home assistance activities with the selection of target participants being residents of the Villa Mutiara Housing Complex. This community service program consists of a series of educational activities to provide knowledge and assistance. This stage begins with monitoring and evaluation activities to assess the initial impact of the socialization that has been carried out. This activity includes direct observation of the residents' residential environment and data collection regarding changes in knowledge and behavior related to healthy homes